Longitudinal oscillations of the sugar beet root crop body at vibrational digging up from soil - V. Bulgakov; I. Holovach; M. Berezovyy (Research in Agricultural Engineering, 2005)
The longitudinal vibrations theory of a continuous elastic body with one fixed extremity is designed. The Ostrogradskii-Hamilton principle of a stationary operation is applied. By Ritz's method the Ritz's equation of frequencies for viewed oscillatory process is obtained. In particular analytical expressions for definition of the first and second fundamental frequencies of body oscillations and forced oscillations amplitude of its any cross-section are obtained.